Contrast‐enhanced sonography for the identification of benign and malignant thyroid nodules: Systematic review and meta‐analysis. Issue 4 (24th September 2015) - Ma, Xuelei; Zhang, Binglan; Ling, Wenwu; Liu, Rongjun; Jia, Hongyuan; Zhu, Fuping; Wang, Mengyao; Liu, Haoqiu; Huang, Jingwen; Liu, Lei
ABSTRACT: Purpose: The use of contrast‐enhanced sonography (CEUS) has yielded promising results in the differentiation of thyroid nodules. We conducted this meta‐analysis to assess its performance in identifying and distinguishing between benign and malignant thyroid nodules. Methods: PubMed, Medline, Embase, and the Cochrane Library were searched for studies published through the end of December 2013. Sensitivity, specificity, positive and negative likelihood ratios, diagnostic odds ratio, and area under the curve were calculated. Results: A total of 13 studies were included in this meta‐analysis. For the diagnosis of malignant thyroid nodules worldwide, the overall mean rates of sensitivity and specificity of CEUS were 90% (95% confidence interval [CI], 88–93%) and 86% (95% CI, 83–89%), respectively. The summary diagnostic odds ratio was 52.83 (95% CI, 21.71–128.55), and the area under the curve for the summary receiver operating characteristic curve was 0.94 (95% CI, 0.90–0.98). Conclusions: This meta‐analysis indicates that CEUS may be a valuable supplemental method, with high rates of sensitivity and specificity, to use for identifying and distinguishing between benign and malignant thyroid nodules. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :199–209, 2016